Effects of Affiliative and Aggressive Humor On Creative Thinking - Rahman, Md Shahinoor; Zhijin, Zhou; Uddin, Muhammad Kamal (Dhaka University Journal of Biological Sciences, 2022)
Previous correlational studies suggest that negative humor style such as aggressive humor style is negatively and positive humor style such as affiliative humor style is positively correlated with creativity. However, it is not yet to experimentally demonstrate the effect of aggressive and affiliative humor on creativity. Therefore, this experimental study was designed to investigate the effect of affiliative humor (AF) and aggressive humor (AG) on creative thinking. The researcher included 60 (38 male, 22 female) participants and randomly assigned 20 in each of AF, AG, and control conditions. To induce humor, theyused12 jokes in each condition. They used Remote Association Task (RAT) for convergent thinking and Alternative Use of task (AUT) for divergent thinking to measure individual creativity. The author expected that (i) people who engage in affiliative humor would perform better at convergent thinking tasks than the control group and the aggressive humor group, (ii) people who engage in affiliative humor would perform better at divergent thinking tasks than the control group and aggressive humor group. Results showed that the affiliative humor successfully induced convergent thinking better than the control group and aggressive humor in the RAT score. Similarly, AF humor successfully induced better creativity than the control group and AG humor group in three components of divergent thinking; fluency, flexibility, and elaboration. However, the mean score of AF humor was better than the AG humor group but not significant. In addition, aggressive humor, likewise affiliative humor, also induced creative thinking in the RAT task and AUT. Thus, the results partially supported all the hypotheses and indicated that in real life, humor induces individual creative thinking whether the humor is positive or negative, it doesn't matter. Both types of humor increase creative thinking. Dhaka Univ. J. Biol. Sci. 31(1): 93-104, 2022 (January)